In vitro micro propagation of Nothofagus alpina through the use of phytohormones - García Cruzatty, Luz (2015)
Nothofagus alpina is one of the most important forest species in the south of Chile and Argentina, where genetic improvement programs have been started. Micropropagation is a very  useful  technique when cloning  trees for improvement purposes, so  the objectives stated in this investigation were: to determine the best of 6-bencilaminopurine phytohormones (BAP) and the ideal culture medium to induce bud rooting and N. alpina nodal section sprouting. Murashige Skoog (MS) and Wood Plant (WPM) media were evaluated  with half macronutrients (rooting) and full micronutrients (multiplication), supplemented with 0.1% peptone, 2.0% saccharose, 0.7% agar and different auxin concentrations. MS medium supplemented with 2 mg L-1 AIB was found to be the best for inducing root formation in both number and  length of the main root. The greatest percentage of rooting was shown by WPM supplemented with 2 mg L-1 AIB. Treatments with cytokinin  for inducing multiplication originated calluses and failed to root, with a prevalence of calluses in WPM medium. The application of cytokinin is not indispensable for sprouting since in witness treatments, a greater number of buds was observed. This leads to the idea that the plant material used contains enough endogenous levels of this phytohormone.